Recurrent Lumbar Disc Herniation: Conventional Re-discectomy Versus TLIF with Unilateral Fixation - Tariq Awad (Egyptian Spine Association, 2016)
Background Data: Recurrent lumbar disc herniation is reported from 5 to 11%. Optimal surgical approach for recurrent disc prolapse is controversial. Some authors believe that repeat discectomy is the treatment of choice, with similar clinical results compared to the primary procedure. Some spine surgeons believe that fusion is necessary for treating disc reherniation. Purpose: Our aim is to compare the clinical outcome in patients with recurrent lumbar disc herniation operated by conventional rediscetomy versus those operated by TLIF with unilateral pedicle screw fixation. Study Design: A descriptive controlled, non-randomized, retrospective, clinical study. Patients and Methods: Forty patients underwent surgery for recurrent lumbar disc herniation. They were divided into two groups; re-discectomy group and TLIF with unilateral fixation group. Each group included 20 patients. They were operated between 2008 and 2016. Participants were evaluated pre-operatively and post-operatively every three months. Operative time, hospital stay and complications were assessed. Pain was scored by a VAS for both lower limbs and back pain. The clinical outcomes were compared using the Prolo economic and functional rating scale. In addition fusion was looked for radiologically. Results: The two groups of patients were fairly homogeneous and comparable. TLIF group showed better clinical outcome parameters including better VAS for low back pain and better Prolo economic, functional rating scale. In comparison the re-discectomy group showed significantly higher complications and reoperation during the follow up period. Conclusion: Patients with recurrent lumbar disc herniation operated by TLIF with unilateral spinal fixation reported less pain & lower disability scores all over the follow up period. This technique is preferable to conventional re-discectomy because it avoids the possibility of recurrence and has less postoperative complications. (2016ESJ124)